Syekh Abdul Wahab Lubis: Tokoh Pendidikan Islam Muara Mais Jambur Tapanuli Selatan (1944-1991) - Abdur Rahman Lubis; Etmi Hardi (Lembaga Yasin AlSys, 2026)
The contribution of local Islamic scholars to the development of Islamic education in Indonesia, particularly in Tapanuli Selatan, warrants examination to strengthen understanding of the history of community-based Islamic education. Although Islamic education in the Mandailing region developed through surau, madrasas, and Islamic boarding schools, studies positioning local figures as the principal drivers of Islamic educational institutions remain relatively limited. Previous studies have generally discussed Syekh Abdul Wahab Lubis as a propagator of Islam in Mandailing Natal, whereas his role as a prominent figure in Islamic education from a historical-biographical perspective has not been comprehensively examined. This study aimed to analyze the life background, struggles, and contributions of Syekh Abdul Wahab Lubis to the development of Islamic education in Muara Mais Jambur during the 1944–1991 period. The study employed the historical method with a biographical approach through the stages of heuristics, source criticism, interpretation, and historiography. Data were obtained through interviews, archives, documents, and various relevant written sources. The results showed that after returning from Darul Ulum Makkah in 1944, Syekh Abdul Wahab Lubis played an active role in developing Islamic education through the organization of majelis taklim, the expansion of da‘wah activities, the establishment of Madrasah Diniyah Awaliyah, and the construction of Pondok Pesantren Darul Ulum. The presence of these institutions contributed to improving the community’s religious understanding, developing generations of Islamic scholars and students, and advancing Islamic education in Muara Mais Jambur. This study concluded that Syekh Abdul Wahab Lubis was a prominent figure in Islamic education who successfully integrated da‘wah, education, and community development in establishing a community-based Islamic education system. These findings contribute to enriching the historiography of local Islamic education and may serve as a reference for research on and the preservation of the history of Islamic scholars in Tapanuli Selatan.